Mark Twain in Japan : the cultural reception of an American icon - Ishihara, Tsuyoshi, 1971- (Mark Twain and his circle series., 2005)
"Explores the history of Mark Twain's reception in Japan in the spheres of books, children's magazines, and anime, the impact of Japanese translations on Twain's public image, how Japanese culture has transformed Japanese versions of Twain's works, and how Japan is culturally influenced by America and America by Japan"--Provided by publisher